Comportamiento de tres variedades de fresa (Fragaria vesca) y tres sustratos en el sistema del cultivo hidropónico - Ayala Duchicela, Martha Marisol (2013)
This research was conducted in the Canton province of Cotopaxi Heart. It lasted four months. At an altitude 1550 m will study three varieties of strawberry (Diamond, Macarena and Carmela) and three substrates 1 (50% sawdust + 25% river sand + rice husk 25%), 2 ( 50% river sand + 25% sawdust + rice husk 25%) y 3 (50% peel shell rice + 25% river sand + 25% sawdust) used a design randomized complete block (RCD) of 9 treatments with three replications. To determine differences between treatment means were used multiple range test of Tukey at 95% probability. In the number of sheets according to Tukey's test p <0.05 statistically significant differences were found at 30 and 60 days only strawberry varieties. While the substrates differed significantly by Tukey test at p <0.05 at 15, 30, 60, 75, 90,105. And only at 75 and 90 days. Found varieties and substrate interactions. At 120 days numerically Diamond and substrate range B3 obtained higher values with 16.42 and 16.47. The force was no significant difference in the varieties according to Tukey's test p <0.05 at 105 days, and the substrates were no significant differences p <0.05 at 45 and 105 days. And only interactions were found at 105 days. At 120 days numerically Diamond and substrate range B3 obtained higher values with 20.0, set the scale considered very good In the flower pendulum significant differences in the varieties according to Tukey test p <0.05 at 45 days. No significant differences in the substrates factor, or interactions as Tukey test at p <0.05. At 60 days numerically and substrate range B3 Macarena higher values obtained with 1.75 and 1.88. In Bloom significant differences in varieties by Tukey test at p <0.05 at 45 days. No significant differences in the factor substrates, we found an interaction by Tukey test at p <0.05 at 120 days. The treatments were the highest numerical value at 60 and 120 days are still A1 B3. Fruiting in significant differences in the varieties according to Tukey's test p <0.05 at 60 days. Significant differences were found in the factor substrates by Tukey test at p <0.05 at 75 days. No interactions were found. The variety diamond progressively obtained numerically increased production dese 45 to 105 days, reaching an average of 2.42. In the fruit diameter were significant differences in the varieties according to Tukey's test p <0.05 at 60 days. No significant differences in factor interactions as substrates or Tukey test at p <0.05. The variety Carmela obtained numerically better fruit diameter at 60 and 120 days, with 8.58 and 7.63 and the best substrate was 8.13 B2 In the fruit weight was not significant difference in the varieties, and substrate interactions as Tukey test at p <0.05. The variety diamond obtained numerically greater weight at 120 days, reaching an average of 16.86. The best performance was achieved in the diamond and the substrate range B3, where for every dollar you get 47 cents.